(7-x)(3.14159265359+2x)=0

Simple and best practice solution for (7-x)(3.14159265359+2x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7-x)(3.14159265359+2x)=0 equation:


Simplifying
(7 + -1x)(3.14159265359 + 2x) = 0

Multiply (7 + -1x) * (3.14159265359 + 2x)
(7(3.14159265359 + 2x) + -1x * (3.14159265359 + 2x)) = 0
((3.14159265359 * 7 + 2x * 7) + -1x * (3.14159265359 + 2x)) = 0
((21.99114858 + 14x) + -1x * (3.14159265359 + 2x)) = 0
(21.99114858 + 14x + (3.14159265359 * -1x + 2x * -1x)) = 0
(21.99114858 + 14x + (-3.141592654x + -2x2)) = 0

Combine like terms: 14x + -3.141592654x = 10.858407346x
(21.99114858 + 10.858407346x + -2x2) = 0

Solving
21.99114858 + 10.858407346x + -2x2 = 0

Solving for variable 'x'.

Begin completing the square.  Divide all terms by
-2 the coefficient of the squared term: 

Divide each side by '-2'.
-10.99557429 + -5.429203673x + x2 = 0

Move the constant term to the right:

Add '10.99557429' to each side of the equation.
-10.99557429 + -5.429203673x + 10.99557429 + x2 = 0 + 10.99557429

Reorder the terms:
-10.99557429 + 10.99557429 + -5.429203673x + x2 = 0 + 10.99557429

Combine like terms: -10.99557429 + 10.99557429 = 0.00000000
0.00000000 + -5.429203673x + x2 = 0 + 10.99557429
-5.429203673x + x2 = 0 + 10.99557429

Combine like terms: 0 + 10.99557429 = 10.99557429
-5.429203673x + x2 = 10.99557429

The x term is -5.429203673x.  Take half its coefficient (-2.714601837).
Square it (7.369063133) and add it to both sides.

Add '7.369063133' to each side of the equation.
-5.429203673x + 7.369063133 + x2 = 10.99557429 + 7.369063133

Reorder the terms:
7.369063133 + -5.429203673x + x2 = 10.99557429 + 7.369063133

Combine like terms: 10.99557429 + 7.369063133 = 18.364637423
7.369063133 + -5.429203673x + x2 = 18.364637423

Factor a perfect square on the left side:
(x + -2.714601837)(x + -2.714601837) = 18.364637423

Calculate the square root of the right side: 4.285398164

Break this problem into two subproblems by setting 
(x + -2.714601837) equal to 4.285398164 and -4.285398164.

Subproblem 1

x + -2.714601837 = 4.285398164 Simplifying x + -2.714601837 = 4.285398164 Reorder the terms: -2.714601837 + x = 4.285398164 Solving -2.714601837 + x = 4.285398164 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.714601837' to each side of the equation. -2.714601837 + 2.714601837 + x = 4.285398164 + 2.714601837 Combine like terms: -2.714601837 + 2.714601837 = 0.000000000 0.000000000 + x = 4.285398164 + 2.714601837 x = 4.285398164 + 2.714601837 Combine like terms: 4.285398164 + 2.714601837 = 7.000000001 x = 7.000000001 Simplifying x = 7.000000001

Subproblem 2

x + -2.714601837 = -4.285398164 Simplifying x + -2.714601837 = -4.285398164 Reorder the terms: -2.714601837 + x = -4.285398164 Solving -2.714601837 + x = -4.285398164 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.714601837' to each side of the equation. -2.714601837 + 2.714601837 + x = -4.285398164 + 2.714601837 Combine like terms: -2.714601837 + 2.714601837 = 0.000000000 0.000000000 + x = -4.285398164 + 2.714601837 x = -4.285398164 + 2.714601837 Combine like terms: -4.285398164 + 2.714601837 = -1.570796327 x = -1.570796327 Simplifying x = -1.570796327

Solution

The solution to the problem is based on the solutions from the subproblems. x = {7.000000001, -1.570796327}

See similar equations:

| (x-4)(0-4)=0 | | 4x^2+26x-14=0 | | (7-x)(pi+2x)=0 | | 4-X^2= | | 4y-10=2 | | x^2+4x+m=0 | | 3r+6=-3 | | 3(5x-6)=-14x-7 | | 0.2x+3=8 | | -8+x=-8 | | 2n+4=26 | | x+1.5=4 | | x+1.5= | | 5x-2x=7x+2x-24 | | 6x+9=4x+21 | | 6A+2A=32 | | 6b-29=36 | | 4x^2-13x+5=-5x+2 | | x^2+5x+17=-5x+1 | | 3d-9-8b=11 | | x^2+7x-1=7 | | n^4-13n^2+36=0 | | 5g*4d= | | 11-8x=0 | | x^2+10x-27=8x-3 | | 5x-33=2x+57 | | =0.4(3d-5) | | -2y+3(-2)+5y+35=6y+2(-2)-3y+8 | | 2x+9y=4 | | 2(-2)-3+5y+6=8y-4(-2)+24 | | 3x+7y=6 | | 9(x-2)-4=14 |

Equations solver categories